2016
DOI: 10.4103/1117-1936.180179
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge regarding Zika virus infection among dental practitioners of tricity area (Chandigarh, Panchkula and Mohali), India

Abstract: ZIKV infection, a new public health emergency, needs to be addressed urgently. All health care professionals should have adequate knowledge of the virus and be conversant with necessary precautionary measures to be taken making it imperative that dental practitioners strive to continually update their knowledge from time to time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 2 publications
2
13
0
Order By: Relevance
“…Even fewer of the participants knew that ZIKV could be transmitted sexually, consistent with previous studies in other countries [20][23],[27]. Thus, few respondents understood that wearing condoms could prevent transmission.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Even fewer of the participants knew that ZIKV could be transmitted sexually, consistent with previous studies in other countries [20][23],[27]. Thus, few respondents understood that wearing condoms could prevent transmission.…”
Section: Discussionsupporting
confidence: 77%
“…Previous research has been conducted on knowledge and perceptions of Zika and ZIKV in several countries including Colombia [19], India [20], Nigeria [21], Qatar [22], as well as in the US [23]. The study in Colombia utilized a convenience sample (n = 269) of participants (healthcare workers and students) in a ZIKA symposium across four locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be explained by the fact that pregnant women whose male sex partner traveled recently had received recent, accurate, and complete information, while others answered correctly because they looked for information from accurate resources, while their educational level might play a role as well. Another study conducted among dental practitioners demonstrated correct knowledge in a small percentage of participants (about 38%) and the factor that significantly associated with knowledge was the postgraduate degree [17]. …”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to evaluate the effectiveness of preventative strategies by KAP surveys among travelers to the affected countries. To our knowledge, three KAP studies have been published for ZVD, and one of them targeted pregnant women in an affected country [16,17,21]. The pack of the WHO for designing and implementing KAP surveys for ZVD and potential complications provides a useful resource for designing and conducting such surveys [11].…”
Section: Discussionmentioning
confidence: 99%